MINIMUM COVERING SEIDEL ENERGY OF A GRAPH - Kanna, Rajesh; R, Jagadeesh; Farahani, Mohammad Reza (IndoMS, 2016)
In this paper we have computed minimum covering Seidel energies ofa star graph, complete graph, crown graph, complete bipartite graph and cocktailparty graphs. Upper and lower bounds for minimum covering Seidel energies of agraphs are also established.DOI :Â http://dx.doi.org/10.22342/jims.22.1.234.71-82